Systemic observation and measurement of microgap formation in dental implant-abutment connection interface under fatigue - Mercan, Cigdem; Bulutsuz, Asli Gunay; Katiboglu, Ahmet Bulent (WALTER DE GRUYTER GMBH, 2023)
Today, a variety of implant designs with different attachment types are widely used in dental implant systems to eliminate connection problems. However, there are still design issues that can significantly affect the long-term success of dental implants. One of these problems is the formation of a microgap in the abutment-implant interface, which can lead to abutment screw loosening, screw fracture, and abutment fracture under masticatory loading. In this in vitro study, the effects of gingival height, dental implant diameter, and abutment type (solid, digital, and ball) on microgap formation were observed after repetitive fatigue tests using an experimental design. After the tests, the optimal design factors were determined to minimize microgap formation. According to the results of the experimental design, the abutment type was found to be the most influential parameter on microgap formation. An implant diameter of 4.1 mm, the smallest gingival height of 0.5 mm, and a digital attachment combination were identified as the optimal design parameters based on the statistical approach (R-2 = 85.3 %).
Keywords: microgap; fatigue test; experimental design; dental implant-abutment interface; measurement; IN-VITRO EVALUATION; BACTERIAL-COLONIZATION; STRESS-DISTRIBUTION; MICROBIAL LEAKAGE; 2-STAGE IMPLANTS; MARGINAL FIT; DIAMETER; LOAD; INFLAMMATION; MICROMOTION; Materials Science